The ecology of “sacred space”: Indie music’s exploration and construction of sacred space in the context of contemporary digital music - Glitsos, Laura (International Association for the Study of Popular Music, 2014)
In this paper I will trace an emerging theme in contemporary indie music centred on the ecology of the ‘sacred space’ within the Ayahuasca ritual, where artists explore and construct traditional notions of place and community. I argue that indie music’s preoccupation with constructing the ecology of sacred space, based on traditional narratives, is a result of the tension emerging from the rise of the digitisation in the context of late-stage capitalism. The virtual space, in some ways, but perhaps not all, is discursively constructed by indie music texts as a profane space, in opposition to the natural, tangible setting of the Ayahuasca ritual. I suggest this may reflect a sense of anxiety toward postmodernity and the virtual age within this demographical musical community.